Analysis of syphilis epidemiological characteristics among the resident population in Ruian City, 2014‒2023 - HONG Wansheng; CHEN Jiangmin; ZHOU Limin; HU Yunlei; CHEN Chunnan; CHEN Liangchai; LI Jun; HUANG Jieru; ZHOU Zumu (Shanghai yufang yixue)
ObjectiveTo understand the epidemiological characteristics of syphilis in Ruian City, so as to provide a scientific basis for developing syphilis prevention and control strategies.MethodsDescriptive epidemiological methods were used to investigate the infection status of syphilis cases reported among the permanent resident population in Ruian City from 2014 to 2023, and its epidemiological characteristics were analyzed.ResultsA total of 5 482 syphilis cases were reported in Ruian from 2014 to 2023, with a male-female ratio of 1∶1.47. The average annual incidence rate from 2014 to 2023 was 37.51/100 000, with a declining trend in the incidence rate among females (APC=-4.78%, P<0.05). The incidence of primary and secondary syphilis decreased, while the proportion of latent syphilis cases increased. No cases of congenital syphilis were reported from 2017 to 2023. The majority of cases (60.29%) were reported among individuals aged 20‒<50 years. In terms of occupation, the highest proportion was found among housekeepers and the unemployed, constituting 42.70% the total cases. Dermatology departments reported the most cases in medical institutions, accounting for 33.38% of the total cases. The most likely route of infection was heterosexual transmission, accounting for 85.84%.ConclusionThe incidence of syphilis among females in Ruian City shows a declining trend, but the overall situation remains concerning. Prevention and control efforts should be intensified among key groups and high-risk populations, along with an enhancement on health education to curb the spread of syphilis.